Thyroid hormone receptor beta in the ventromedial hypothalamus is essential for the physiological regulation of food intake and body weight - Hameed,S; Patterson,M; Dhillo,W; Rahman,S; Ma,Y; Holton,C; Gogakos,A; Yeo,G; Lam,B; Polex-Wolf,J; Fenske,W; Bell,J; et al. (Cell Reports, 2017)
The obesity epidemic is a significant global health issue. Improved understanding of the mechanisms that regulate appetite and body weight will provide the rationale for the design of anti-obesity therapies. Thyroid hormones play a key role in metabolic homeostasis through their interaction with thyroid hormone receptors (TRs), which function as ligand-inducible transcription factors. The TR-beta isoform (TRβ) is expressed in the ventromedial hypothalamus (VMH), a brain area important for control of energy homeostasis. Here, we report that selective knockdown of TRβ in the VMH of adult mice results in severe obesity due to hyperphagia and reduced energy expenditure. The observed increase in body weight is of a similar magnitude to murine models of the most extreme forms of monogenic obesity. These data identify TRβ in the VMH as a major physiological regulator of food intake and energy homeostasis.